Genetic structure of brown and Iberian hare populations in northern Iberia: Implications for conservation of genetic diversity. Issue 4 (16th April 2014) - Sanz‐Martín, María J.; Estonba, Andone; Manzano, Carmen; Iriondo, Mikel; Pérez‐Suárez, Gonzalo; Fernández, Alfonso; Palacios, Fernando
ABSTRACT Hares in the northern Iberian Peninsula have been managed by local authorities primarily as a game species for hunting. Over the last 4 decades, populations have been restocked by means of translocation from other regions. We examined the genetic structure of wild populations of 2 species living in the northern Iberian Peninsula: the brown hare (Lepus europaeus) and the Iberian hare (L. granatensis) to assess their genetic uniqueness and distinctiveness, and thus determine if these populations have been altered by anthropogenic translocations. We analyzed 215 sequences of the mitochondrial DNA (mtDNA) control region and 6 microsatellite markers in 157 individuals from northern Iberia. We detected 3 distinct mtDNA types in L. europaeus (timidus, granatensis, and europaeus mtDNA lineages) and 2 mtDNA types in L. granatensis, (timidus and granatensis lineages). The high and homogeneous prevalence of a north European timidus mtDNA lineage in both L. europaeus and L. granatensis may be the result of an ancient introgression during the last glacial period. The homogeneous distribution of the granatensis mtDNA lineage in L. europaeus may also be the result of gene flow between species in a contact zone. In contrast, both the low prevalence of the europaeus mtDNA lineage and its highly localized presence in the center of Guipúzcoa are strongly indicative of the recent incorporation of non‐Iberian L. europaeus into the local population. The data derived from microsatellite markers revealed that L. europaeus populations from the center of Guipúzcoa had a much higher assignment probability to eastern European populations than the rest of northern Iberian populations, which presented high assignment probabilities to the populations from protected areas of Cantabria and Huesca. Strict adherence to International Union for Conservation of Nature (IUCN) criteria strongly suggests that these translocations may not be beneficial, in that they compromise the genetic integrity of the native population of L. europaeus in the northern Iberian Peninsula. For this reason, we strongly recommend 1) translocations of L. europaeus individuals from non‐Iberian populations into Iberian populations be avoided; 2) restocking the center of Guipúzcoa with autochthonous L. europaeus individuals; 3) carrying out periodic genetic surveys of L. europaeus throughout the study area; and 4) increasing our knowledge of the genetic structure of L. granatensis under natural conditions. © 2014 The Wildlife Society.